ANALYSIS OF STRATEGIES FOR RESOLVING PROBLEMATIC FINANCING IN REDUCING THE NON-PERFORMING FINANCING (NPF) RATIO: A CASE STUDY OF PT BANK SUMUT SHARIA SUB-BRANCH OFFICE RANTAUPRAPAT - Lubis, Jainuar Amarullah; Syafina, Laylan; Syahbudi, Muhammad (International Journal of Cultural and Social Science, 2026)
This study aims to analyze strategies for resolving problematic financing in an effort to reduce the Non-Performing Financing (NPF) ratio at PT Bank Sumut Sharia Sub-Branch Office (KCPS) Rantauprapat. The research employs a qualitative approach using a case study method, with data collected through interviews, observations, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings indicate that the implementation of problematic financing resolution strategies through three main approaches preventive strategies, curative strategies, and execution strategies has proven to be effective. This effectiveness is evidenced by a decline in the NPF ratio from 3.7% in 2021 to 3.0% in 2024. The study concludes that integrated and consistently implemented strategies for resolving problematic financing are capable of reducing NPF levels, maintaining financial stability, and enhancing public trust in Islamic banking.